2009
DOI: 10.1111/j.1447-0594.2009.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Trail Making Test and physical performance in elderly Japanese

Abstract: The TMT reflects complex walking performance, so it can be a useful synthetic indicator for health programs promoting independence in elderly Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…These results support previous studies in the field (Ble et al, 2005; Coppin et al, 2006; Hirota et al, 2010; Hobert et al, 2011; Killane et al, 2014) Accordingly, for the CWP, the absolute values of single- and dual-task performances revealed group differences similar to the observed differences on SWP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results support previous studies in the field (Ble et al, 2005; Coppin et al, 2006; Hirota et al, 2010; Hobert et al, 2011; Killane et al, 2014) Accordingly, for the CWP, the absolute values of single- and dual-task performances revealed group differences similar to the observed differences on SWP.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Lowry found that cognitive flexibility was related to the number of steps performed in a single-task Figure-of-8 Walk Test (F8WT) (Lowry et al, 2012), whereas another study found no associations between cognitive flexibility and the F8WT (Odonkor et al, 2013). Some studies have found that cognitive flexibility is associated with gait speed in dual tasking among older people, especially for walking paths with increasing complexity that are more cognitively demanding (Ble et al, 2005; Coppin et al, 2006; Hirota et al, 2010; Hobert et al, 2011; Killane et al, 2014). Taken together, there is (i) very limited knowledge about the influence of different walking situations on prioritization strategies, and (ii) evidence that cognitive flexibility is associated with prioritization strategies and thus cognitive flexibility seems a promising marker to investigate prioritization.…”
Section: Introductionmentioning
confidence: 99%
“…However, we could not confirm the type of dementia, such as Alzheimer or Lewy body dementia. We also could not determine the severity of dementia because our administrative [34]. Therefore, our identification using the ICD-10 code may have underestimated the number of elderly patients with dementia.…”
Section: Discussionmentioning
confidence: 91%
“…The HVLT-R is a learning and memory test, in which the patient was asked to learn and recall a list of 12 words over three trials [18]. The TMT is a measure of graphomotor speed and set-shifting to measure the executive function [19]. The COWA Test provides a relatively quick test of verbal fluency and it is believed to place high demands on executive control processes [20].…”
Section: Methodsmentioning
confidence: 99%